Diabetes Mellitus and Mortality among COVID-19 Patients in Jakarta, March-August 2020 - Wulandari, Endang Widuri; Rotnoatmodjo, Sudarto; Salama, Ngabila (UI Scholars Hub, 2022)
Diabetes mellitus (DM) comorbidity is one of the risk factors for coronavirus disease 2019 (COVID-19) mortality. This study aimed to determine the association of comorbid DM and mortality among COVID-19 confirmed cases in DKI Jakarta Province, controlled with confounding variables from March to August 2020. The study design was a retrospective cohort using cox proportional hazard regression, with a total sample of 1,480. The data consisted of 740 COVID-19 cases with and 740 without comorbid DM. The inclusion criteria were COVID-19 confirmed cases with polymerase chain reaction (PCR) laboratory testing reported to the DKI Jakarta Provincial Department of Health, and the exclusion criteria were pregnant women. The study result indicated that the Crude Hazard Ratio (CHR) of DM and mortality among COVID-19 confirmed cases was 7.4 (95% CI = 4.5-12.3, p-value50 years).